Conjugation of testosterone modifies the interaction of mono-functional cationic platinum(II) complexes with DNA, causing significant alterations to the DNA helix. - Sanchez-Cano, C; Huxley, M; Ducani, C; Hamad, A; Browning, M; Navarro-Ranninger, C; Quiroga, A; Rodger, A; Hannon, M (2010)
Previously a range of androgen conjugates with non-conventional platinum(II) complexes have been synthesised with the aim of enhancing cellular delivery, and which have shown increased cytotoxic activity compared with non-steroidal compounds (M. J. Hannon et al., Dalton Trans., 2010, DOI: 10.1039/c0dt00838a). To further study this, the complexes have been assessed for their ability to bind to and alter the structure of DNA. All platinum(II) complexes studied herein bind to model nucleo-bases and DNA, but to our surprise, testosterone-based complexes caused the DNA helix to undergo significant unwinding and bending, whereas non-steroidal control complexes caused minimal structural alterations. These effects are similar to those cisplatin induces on DNA structure despite the fact that these compounds produce a monofunctional lesion. This ability attributed to interactions between the DNA helix and bulky steroidal skeleton of testosterone, coupled with the enhanced cellular delivery induced by the steroid make the steroid approach an exciting way to explore non-conventional platinum drug delivery.